Double-gate metal–oxide TFT pixel circuit for improved luminance uniformity of mobile OLED display - YiKyoung You; Kook Chul Moon; HyeongMin Kim; JungSuk Oh; SangWoon Lee; Jun Hyung Lim; Kyoung Seok Son; JaeHyung Cho; KeeChan Park (Journal of Information Display)
The small subthreshold swing (SS) of metal–oxide (MOx) thin-film transistors (TFTs) reduces the data voltage (VDAT) range of the organic light-emitting diode (OLED) display pixel circuit. This leads to a large OLED current error when a small change occurs in the gate-to-source voltage (VGS) of the driving TFT in the pixel. Therefore, we propose a new pixel circuit adopting a double-gate TFT structure for the driving TFT, which is mainly driven by the bottom gate with a thicker gate insulator to provide a wide VDAT range. The proposed pixel circuit further expands the VDAT range by employing threshold voltage (VTH) modulation effect depending on the gray level. It also allows for flexible adjustment of the VTH extraction time to reduce OLED current error at low gray levels. SPICE simulation and measured results verify that the proposed pixel circuit reduces the OLED current error rate to less than 10% even with a VTH variation of ±0.5 V or SS variation of ±5% for the current level from 0.1 nA to 30 nA.